Penerapan Backward Design Model Dalam Matakuliah Basic Science Untuk Meningkatkan Literasi Guna Membangun Wawasan Kristen Alkitabiah - Kurniawati Martha (Sekolah Tinggi Theologia Nazarene Indonesia, 2021)
Technology helps us to get information in a short time. With an internet connection, we can easily get any information. But there is an emergency literacy problem in Indonesia. The question that arises in the minds of researcher is,